Effect of diuretics on fetal growth: A drug effect or confounding by indication? Pooled Danish and Scottish cohort data - Olesen, Charlotte (Blackwell Science Inc, 2001)
AIMS: The diabetogenic effect of diuretics, as well as the indication for prescribing them, may impact on fetal growth. We analysed whether the purchase of prescription drugs for diuretics during pregnancy was associated with measures of fetal growth. METHODS: During 1991–98 all women who purchased prescription drugs for diuretics during pregnancy were identified in the Northern Jutland Prescription Database (NJDP), Denmark, and in the Medicines Monitoring Unit's Database (MEMO), Scotland. Information on birth weight and gestational age was obtained from the Danish Birth Registry, the Danish Hospital Discharge Registry and the Scottish Tayside Neonatal Database. Information on diabetes, hypertension and prepregnancy weight were obtained by hospital record review in a sample of women in the Danish cohort. Women who did not purchase prescription diuretics during pregnancy were used as a reference group in both cohorts. RESULTS: Danish women who purchased prescription loop diuretics during pregnancy gave birth to infants with higher birth weights than women who did not use diuretics; mean difference 104.7 g (95% CI; 2.6, 206.9). However, the high prevalence of diabetes (10.3%) among Danish women who purchased prescription loop diuretics during pregnancy might explain this result. Both the Danish and the Scottish women who purchased prescription diuretics during their pregnancy were at increased risk of preterm delivery (< 37 completed weeks); ORs: 1.8 (CI; 1.2, 2.7)(NJDP), 1.9 (CI; 0.9, 4.3)(MEMO). The proportion of hypertension among women who purchased prescription thiazides was 15.8%, and the risk of having an infant with a birth weight (BW) < 2500 g was increased; ORs: 2.6 (CI; 1.4, 5.0)(NJDP), 2.4 (CI; 0.8, 7.8)(MEMO.) CONCLUSIONS: Prescribing diuretics during pregnancy was associated with differences in birth weight and incidence of preterm delivery. Confounding by indication may explain the findings.